MAKSI for ICT-based accounting learning at vocational high schools - Vivi Pratiwi; Moh. Danang Bahtiar; Han Tantri Hardini (Jurnal Pendidikan Vokasi, 2019)
This study aims to produce ICT-based learning media for Vocational High Schools (VHS) in the form of ICT-based accounting multimedia application, named "Multimedia Akuntansi" (MAKSI) on bank reconciliation material. The development of learning media is done because of the limited number of innovative learning media available for VHS students, especially in the accounting field. The condition is influential on the students' low level of understanding. This research was research and development using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The use of the ADDIE model is because the model is flexible, so it can be used for learning instrument development. At each phase of development, evaluation and revision were conducted so that the resulting product became a valid and reliable product. This development resulted in MAKSI proven to be suitable for use in accounting learning. The feasibility of MAKSI was evaluated from the average score of product feasibility validation from the material expert by 87%, from the media expert of 96%, and the result of the students' evaluation by 88.7%. MAKSI can help the learning process more enjoyable so that the media is interesting and proven to improve students' understanding significantly. MAKSI can be a complement, alternative, and variation of learning media in VHS. This product can be operated via laptops/computers as well as smartphones through free downloads in Play Store. The utilization of MAKSI is in accordance with the curriculum demand on the utilization of ICT in the learning process to support independent and student-centered learning.